THE ROLE OF RELIGIOSITY IN ENHANCING FRAUD PREVENTION EFFECTIVENESS AT BANK MUAMALAT EAST JAVA: IMPLEMENTATION OF GCG, INTERNAL CONTROL AND COMPENSATION ADEQUACY - Yusrik Ihza Manggara; Ronny Malavia Mardani; Ridwan Basalamah (RADJA PUBLIKA, 2025)
This study aims to analyze the role of religiosity in enhancing fraud prevention effectiveness through the implementation of Good Corporate Governance (GCG), internal control, and compensation adequacy at Bank Muamalat East Java. Using a quantitative approach with Structural Equation Modeling method through Smart PLS, this study involved 74 respondents from Bank Muamalat East Java employees. Research variables include religiosity (ideological, ritualistic, consequential, intellectual, experiential), GCG (transparency, accountability, responsibility, independence, fairness), internal control (control environment, risk management, control activities, information and communication, monitoring), compensation (salary, incentives, allowances, facilities, non-financial compensation), and fraud prevention (lapping, embezzlement, pilferage, falsification, skimming). The results show that religiosity plays a significant role as a moderator in strengthening the relationship between GCG, internal control, and compensation adequacy toward fraud prevention. The research model explains 74.2% of variance in fraud prevention with predictive relevance (Q²) of 0.531. These findings provide theoretical contributions in developing fraud triangle theory enriched with religiosity dimensions in the Islamic banking context. Practically, this study provides recommendations for Bank Muamalat management to integrate religiosity values into governance systems, internal control, and compensation policies as a comprehensive fraud prevention strategy. Keywords: religiosity, fraud prevention, good corporate governance, internal control, compensation, Islamic banking .